Perancangan Sistem Informasi Desa Bintang Sidikalang (Sidesta) Berbasis Web - Dewi, Sri; Perdana, Adidtya; Harliana, Putri; Surbakti, Nurul Maulida (J-INTECH (Journal of Information and Technology), 2023)
An information system is a collection of elements that are interrelated and work together to process input to produce the desired output. It is hoped that the development of a web-based information system at the Bintang Village Office can help increase information updates and expand the reach of information that can be disseminated to the community. Implementation of System Management Design is an important part of the system implementation process, so that the system design process can be structured in a structured manner and avoid errors in design. Based on the research results, it was concluded that a website-based Bintang Village Information System had been built using the UML (Unified Modeling Language) system design method and the PHP programming language. From the test results using the Black Box method, it can be concluded that the development of the Bintang Village Information System is functionally running well and in line with expectations. The information system that was built has been able to provide convenience in obtaining effective and efficient information for the people of Bintang Village.